Strategi Pengelolaan Sumber Daya Manusia untuk Menekan Perpindahan Tugas Pegawai - Sari, Intan Permata; Novalinda, Novalinda; Syafwandi, Syafwandi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to find out human resource management strategies to reduce the transfer of employee duties. This research is a qualitative descriptive research, descriptive research does not provide treatment, manipulation or alteration to the variables studied, but describes a condition as it is. Data collection is carried out through observation, interviews, and documentation. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. As a result of the previous discussions, the author concludes that effective HR management strategies to suppress the transfer of employee duties are a key factor in the success of the organization. By implementing the right strategies in human resource management, organizations can reap significant benefits, from increased productivity to better employee retention. It is important for organizations to continue to improve strategies in effective human resource management to reduce the transfer of employee duties in accordance with the development of the times and employee needs.